Evaluation of the Relationship between Internet Addiction and the Thoracal Kyphosis Angle on Medical Faculty Students - Keziban Karacan; Halit Çelik; Mehtap Erdoğan (Journal of Contemporary Medicine, 2021)
AIM: For the last 20 years, various problems caused by internet has brought attention to researchers. People who actively use the Internet can spend 40 to 80 hours per week on a computer or phone. Their sleep patterns, daily life and exercise habits change over time. These changes bring along some illnesses such as back pain, neck pain and carpal tunnel syndrome. Many of these ailments underlie postural disorders. The most common of these postural disorders is increased thoracic kyphosis. Our aim is to determine the effect of internet usage on thoracic kyphosis angle in healthy individuals.